Anisotropic structures of some microorganisms studied by polarization microscopy - Žižka, Zdeněk (Folia microbiologica, 2014)
Polarization microscopy has been used to study the internal structures of microbial cells and in terms of the birefringence of these structures and its possible relation to the cell function and composition. Cyanobacteria of the genus Phormidium were found to contain no anisotropic structures, while other microorganisms were found to contain them, albeit to a different extent, size, and number. The flagellate Euglena was found to contain two large anisotropic bodies, whereas the flagellate of the genus Phacus belonging to the same systematic group Euglenales was observed to contain only one large anisotropic body (storage substances--paramylon). On the other hand, green algae of the genus Scenedesmus, whose cells form four--celled coenobia, contained clusters of small anisotropic granules composed also of storage substances (volutin). Minute anisotropic granules (storage substances) in two smaller clusters were found also in diatoms of the genus Navicula, whereas the green alga of the genus Mougeotia was revealed to contain, in addition to minute anisotropic granules (storage substances) occurring in low numbers in the cytoplasm, also a strongly birefringent cell wall (shape birefringence). Cells of the amoeba of the genus Naegleria and heliozoans of the genus Heterophrys were observed to contain only isolated tiny anisotropic granules (storage substances).
Keywords: Cyanobacteria; Microscopy, Polarization; Organelles; Anisotropy; sinice; Eukaryota; organely; polarizační mikroskopie; anizotropie